Causes of death in rural adult population of North India (2002-2007), using verbal autopsy tool - C Palanivel; Kapil Yadav; Vivek Gupta; Sanjay K Rai; Puneet Misra; Anand Krishnan (Wolters Kluwer Medknow Publications, 2013)
Background: With the on-going epidemiological transition, information on the pattern of mortality is important for health planning. Verbal autopsy (VA) is an established tool to ascertain the cause of death in areas where routine registration systems are incomplete or inaccurate. We estimated cause-specific mortality rates in rural adult population of 28 villages of Ballabgarh in North India using VA. Materials and Methods: During 2002-2007, trained multi-purpose health workers conducted 2294 VA interviews and underlying cause of death was coded by physicians. Proportional mortality (%) was calculated by dividing the number of deaths attributed to a specific cause by the total number of deaths for which a VA was carried out. Findings: 61% of deaths occurred among males and 59% occurred among those aged ≥60 years. The leading causes of death were diseases of the respiratory system (18.7%) and the circulatory system (18.1%). Infectious causes and injuries and other external causes, each accounted for around 15% of total deaths followed by neoplasms (6.8%) and diseases of the digestive system (4%). Among those 45 years of age or more than half of deaths were attributed to non-communicable diseases (NCDs) alone. Accidents and injuries were responsible for one-fourth of deaths in 15-30 years age group. Conclusion: NCDs and injuries are emerging as major causes of death in this region thereby posing newer challenges to public health system.